The utilization and accessibility of campus open space: a case study of the west campus of CAU - Chuanyang Pan; Xu Feng; Lin Wang; Maolin Wu; Minyuan Wang (Journal of Asian Architecture and Building Engineering)
The rational configuration of campus open space is essential for promoting students’ mental health and general well-being. To facilitate the efficient utilization and layout optimization of campus open space, a comprehensive examination of the utilization patterns and accessibility of campus open space in the West Campus of China Agricultural University (CAU) was conducted through field research, questionnaire analysis and space syntax. The findings reveal that: (1) There is a notable imbalance in the utilization of campus open space, with walk-through being the most prevalent, selected by 86.9% of users, underscoring the demand for convenient transportation options. (2) The distribution of road accessibility strongly correlates with the classification of roads, and discrepancies were observed in the accessibility of open spaces at three levels. Those with high accessibility were situated in proximity to core areas and multiple main axes. (3) The accessibility of all external roads and external roads adjacent to entrances represents a critical factor influencing crowd behavior, with coefficients of 0.255 and 0.218 (p < 0.10). In addition, landscape quality, cultural atmosphere and other aspects are pivotal in maintaining user engagement. These insights offer a novel perspective for the planning, design, and optimization of campus open spaces.